Functional disability trajectories at the end of life among Japanese older adults: findings from the Japan Gerontological Evaluation Study (JAGES). (20th November 2022) - Saito, Junko; Murayama, Hiroshi; Ueno, Takayuki; Saito, Masashige; Haseda, Maho; Saito, Tami; Kondo, Katsunori; Kondo, Naoki
Abstract: Background: this study aimed to identify distinct subgroups of trajectories of disability over time before 3 years of death and examine the factors associated with trajectory group membership probabilities among community-dwelling Japanese older adults aged 65 years and above. Methods: participants included 4, 875 decedents from among community-dwelling Japanese older adults, aged ≥ 65 years at baseline (men: 3, 020; women: 1, 855). The certified long-term care levels of the national long-term care insurance (LTCI) system were used as an index of functional disability. We combined data from the 2010 Japan Gerontological Evaluation Study and data from the 2010 to 2016 LTCI system. Group-based mixture models and multinominal logistic regression models were used for data analysis. Results: five distinct trajectories of functional disability in the last 3 years of life were identified: 'persistently severe disability' (10.3%), 'persistently mild disability' (13.0%), 'accelerated disability' (12.6%), 'catastrophic disability' (18.8%) and 'minimum disability' (45.2%). Multinominal logistic regression analysis found several factors associated with trajectory membership; self-rated health was a common predictor regardless of age and gender. The analysis also showed a paradoxical association; higher education was associated with trajectory group membership probabilities of more severe functional decline in men over 85 years at death. Conclusions: individual perception of health was a strong predictor of trajectories, independent of demographic factors and socio-economic status. Our findings contribute to the development of policies for the long-term care system, particularly for end-of-life care, in Asian countries.